The efficacy of saffron supplementation on inflammation and oxidative stress in patients with type-2 diabetes mellitus: a meta-analysis - Qin, Lulu; Hu, Nini; Wang, Kejing; Chen, Lin (Frontiers in Endocrinology, 2025)
BackgroundIn this study, a meta-analysis was performed to evaluate the changes in the levels of inflammation and oxidative stress levels in type 2 diabetes mellitus (T2DM) patients after saffron supplementation.MethodsA comprehensive and systematic investigation was carried out to identify relevant studies on PubMed, Web of Science, The Cochrane Library, and EMBASE databases. The investigation aimed to find studies that tested the efficacy of saffron supplements in reducing inflammation and oxidative stress in people with type 2 diabetes. The data were synthesized using Revman 5.4 software to perform a meta-analysis.ResultsA total of five relevant articles involving 261 patients were included. The meta-analysis results demonstrated a significant reduction in TNF-α levels following saffron supplementation compared to the placebo group. However, no significant changes were observed in the levels of CRP levels (SMD: 0.01, 95% CI: −0.52 to 0.05, p = 0.97), IL-10 levels (SMD: 0.31, 95% CI: −0.05 to 0.67, p = 0.09), IL-6 levels (SMD: −0.28, 95% CI: −0.79 to 0.24, p = 0.29), MDA levels (SMD: 0.01, 95% CI: −0.28 to 0.30, p = 0.95), and TAC levels (SMD: −0.09, 95% CI: −0.42 to 0.24, p = 0.59).ConclusionThe findings of this meta-analysis provide compelling evidence to support the efficacy of saffron supplementation in reducing the effects of TNF-α levels in individuals with T2DM. Nevertheless, the present body of research is still limited in its ability to establish the precise impact of saffron supplementation on oxidative stress and other inflammatory factors in T2DM patients.